Enhanced capacity of women in Smart-Valleys, alternate wetting and drying and multi-stakeholders platforms establishment in Mali - Dossou-Yovo, Elliott Ronald; Djagba, Justin; Koné, Pierre; Akpoffo, M. Marius; Doumbia, Salif (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Mali, situated in the Sahelian region of West Africa, faces vulnerability to the impacts of climate change, and these effects are already evident across various sectors. Noteworthy consequences of climate change in Mali encompass heightened temperatures, increased frequency of droughts, water scarcity, and the progression of desertification. Indirect impacts include health impacts, such as the spread of vector-borne diseases, and resource conflicts, exacerbating existing tensions arising from diminishing resources.